Evaluation of passive integrated transponder tag retention from two tagging locations in juvenile pallid sturgeon. (23rd November 2012) - Hamel, M. J.; Steffensen, K. D.; Hammen, J. J.; Pegg, M. A.
Summary Population augmentation and propagation of pallid sturgeon (Scaphirhynchus albus) have been a focus of scientists since the mid‐1990s. Various tag types have been used to gain a better understanding of population characteristics, stocking success, and movement patterns. Passive integrated transponder (PIT) tags have been consistently used since the inception of recovery efforts to mark age‐1 and older pallid sturgeon. This tag has been successfully used with other sturgeon species, and tagging protocols for pallid sturgeon were developed in response to those successes. Tag retention rates in pallid sturgeon have been reported as variable or unknown and there has been no formal study to determine PIT tag retention in pallid sturgeon, particularly with age‐1 individuals that are propagated in hatcheries to be stocked into the wild. The objective was to evaluate retention rates of PIT tags inserted into the operculum and along the base of the dorsal fin of age‐1 pallid sturgeon (total fork length [FL] range = 214–358 mm). Tagged sturgeon (n = 80) were held in a large holding tank and inspected for tag loss twice a month for a total of 189 days. Final tag retention was 83% for tags inserted into the operculum and 85% for tags inserted near the dorsal fin. Tags shed from the operculum were from smaller fish (mean FL = 265 mm) and losses occurred during the first 60 days of the experiment. Tags shed from the dorsal site were predominantly from larger individuals (mean FL = 305 mm) and losses were continual throughout the experiment. Future research should determine size‐specific tag retention rates so that hatcheries can maximize retention in either tag placement location.